A decade of energy and mass balance investigations on the glacier Kongsvegen, Svalbard. Issue 10 (21st May 2013) - Karner, F.; Obleitner, F.; Krismer, T.; Kohler, J.; Greuell, W.
Abstract: [1] Kongsvegen is an Arctic glacier located in northwest Spitzbergen. We use meteorological observations made near the average equilibrium line of Kongsvegen during the decade 2001 to 2010 to drive a glacier energy and mass balance model. Average daily and seasonal cycles are analyzed over the course of a full decade, as well as the interannual variations of the meteorological parameters and of the mass and energy balance components. The calculated average of net radiation is close to zero and the sensible heat flux is the most important and continuous source of energy at the surface. The latent heat flux is a weak source of energy as well. The resultant flux constellation yields a surplus of energy accumulating throughout the decade (9.5 W m –2 ) and fosters a negative specific surface mass balance throughout the investigated decade (–1.8 m w. eq.). The most significant mass loss occurred during the middle of the decade (2004 until 2006), with positive surface mass balances observed afterward when significant amounts of superimposed ice were formed. This development is well correlated to the total surface mass balance of the glacier. Application of monthly temperature and precipitation perturbations corroborates earlier studies indicating a high sensitivity of the mass balance to energy fluxes depending on temperature conditions during summer. Key Points: Evaluation of a decadal meteorological record of an Arctic glacier Use of SOMARS, validation of results, investigations of climate sensitiviy Annual, monthly, daily consideration